Student Attitudes Contribute to the Effectiveness of a Genomics CURE - Lopatto, David; Rosenwald, Anne G.; Burgess, Rebecca C.; Silver Key, Catherine; Van Stry, Melanie; Wawersik, Matthew; DiAngelo, Justin R.; Hark, Amy T.; Skerritt, Matthew; Allen, Anna K.; Alvarez, Consuelo; Anderson, Sara; et al. (Journal of microbiology & biology education, 2022)
The Genomics Education Partnership (GEP) engages students in a course-based undergraduate research experience (CURE). To better understand the student attributes that support success in this CURE, we asked students about their attitudes using previously published scales that measure epistemic beliefs about work and science, interest in science, and grit. The Genomics Education Partnership (GEP) engages students in a course-based undergraduate research experience (CURE). To better understand the student attributes that support success in this CURE, we asked students about their attitudes using previously published scales that measure epistemic beliefs about work and science, interest in science, and grit. We found, in general, that the attitudes students bring with them into the classroom contribute to two outcome measures, namely, learning as assessed by a pre- and postquiz and perceived self-reported benefits. While the GEP CURE produces positive outcomes overall, the students with more positive attitudes toward science, particularly with respect to epistemic beliefs, showed greater gains. The findings indicate the importance of a student’s epistemic beliefs to achieving positive learning outcomes.